Review essay: Going Round in Circles': Michel Cuypers, The Composition of the Qur'an: Rhetorical Analysis, and Raymond Farrin, Structure and Qur'anic Interpretation: A Study of Symmetry and Coherence in Islam's Holy Text - Sinai, N (Edinburgh University Press, 2017)
Since the 1980s, scholars publishing in Western languages have increasingly learnt to appreciate the literary qualities of the Qur’anic proclamations, thereby parting ways with the dismissive comments made by some earlier Western readers of the Islamic scripture. At the forefront of this development stands the question of whether Qur’anic surahs can be considered to display a significant degree of thematic and literary coherence. Do the surahs, or at least some of them, constitute compositional unities or are they merely collocations of self-contained verses or, at most, verse clusters? The fact that much pre-modern Islamic exegesis exhibits little interest in the surahs’ structural organisation above the verse level and often attributes individual verses to distinct historical situations in the life of Muhammad creates a certain drift towards the latter alternative. Nonetheless, it seems that the current consensus among scholars based at European and North American universities has largely been swung in favour of at least some degree of surah holism. This is undoubtedly a welcome and justified development.